2000
DOI: 10.2134/jeq2000.00472425002900040010x
|View full text |Cite
|
Sign up to set email alerts
|

Virus Transport through Saturated Sand Columns as Affected by Different Buffer Solutions

Abstract: To accurately examine the mechanisms that control virus retention and transport in porous media, it is essential to perform experiments under environmentally relevant conditions. Laboratory studies of virus transport are generally conducted using buffered solutions. However, there are no standards for the concentration and composition of the solution, making comparisons between different studies difficult. Our objective was to systematically investigate the effects of the ionic strength and composition of buff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 0 publications
4
46
0
Order By: Relevance
“…The physical processes such as advection, dispersion, diffusion, straining and physical filtration, adsorption and biological processes such as growth/ decay processes and include active adhesion/detachment, survival and chemotaxis are strongly affected on biocolloid transport in saturated and unsaturated porous media. Although there is a substantial body of published research on biocolloidal transport in the subsurface, much of it focuses on transport in the saturated zone (e. g. Bales et al 1989;Chu et al 2000;Chu et al 2001;Fontes et al 1991;Harvey 1997;Hornberger et al 1992;McCarthy and McKay 2004;McKay et al 1993;Sen and Khilar 2006;Sen and Khilar 2009;Sen et al 2004) rather than on transport in the unsaturated vadoze zone. In the unsaturated porous media, the additional mechanisms (compared with saturated zone) for colloid transport are reported as: colloid captured at the liquid-gas interface (Crist et al 2004;2005;Gao et al 2008;Zevi et al 2005), colloid capture due to straining (Wan and Tokunaga 1997;Bradford et al 2006, colloid captured at solid-liquid-gas interface (Williams and Berg 1992;Abdel-Fattah and El-Genk 1998;Sirivithayapakorn and Keller 2003;Lazouskaya and Jin 2006) and colloid storage in immobile zone (Cherrey et al 2003;Gamerdinger and Kaplan 2001;Gao et al 2006), respectively.…”
Section: Major Subsurface Processes On Biocolloid Transportmentioning
confidence: 99%
“…The physical processes such as advection, dispersion, diffusion, straining and physical filtration, adsorption and biological processes such as growth/ decay processes and include active adhesion/detachment, survival and chemotaxis are strongly affected on biocolloid transport in saturated and unsaturated porous media. Although there is a substantial body of published research on biocolloidal transport in the subsurface, much of it focuses on transport in the saturated zone (e. g. Bales et al 1989;Chu et al 2000;Chu et al 2001;Fontes et al 1991;Harvey 1997;Hornberger et al 1992;McCarthy and McKay 2004;McKay et al 1993;Sen and Khilar 2006;Sen and Khilar 2009;Sen et al 2004) rather than on transport in the unsaturated vadoze zone. In the unsaturated porous media, the additional mechanisms (compared with saturated zone) for colloid transport are reported as: colloid captured at the liquid-gas interface (Crist et al 2004;2005;Gao et al 2008;Zevi et al 2005), colloid capture due to straining (Wan and Tokunaga 1997;Bradford et al 2006, colloid captured at solid-liquid-gas interface (Williams and Berg 1992;Abdel-Fattah and El-Genk 1998;Sirivithayapakorn and Keller 2003;Lazouskaya and Jin 2006) and colloid storage in immobile zone (Cherrey et al 2003;Gamerdinger and Kaplan 2001;Gao et al 2006), respectively.…”
Section: Major Subsurface Processes On Biocolloid Transportmentioning
confidence: 99%
“…McCarthy and McKay [18] and Sen et al [122] mentioned in their article that there is a substantial body of published research on microbial transport in the subsurface, much of it focuses on transport in the saturated zone [119][120][121][122][123][124][125][126][127][128][129][130][131][132][133][134]. Transport of bacteria in porous media is mainly bounded with small scale batch and column studies.…”
Section: Biocolloids Transportmentioning
confidence: 99%
“…Previous studies found the breakthroughs of MS2 were more retarded [20] and recoveries of MS2 were lower [21] under higher IS conditions. However, the attachment of different viruses may respond differently to IS, for example, the recovery of X174 remained the same in higher IS buffer [21].…”
Section: Introductionmentioning
confidence: 82%
“…Ionic strength (IS) is known to have significant influence on microbial and virus transport behaviors [19][20][21][22] and a wide range of IS is present in different environmental waters such as rivers, lakes, estuaries and oceans. Previous studies found the breakthroughs of MS2 were more retarded [20] and recoveries of MS2 were lower [21] under higher IS conditions.…”
Section: Introductionmentioning
confidence: 99%